Rancang Bangun Sistem Informasi Pemesanan Makanan Dan Minuman Berbasis Web (Studi Kasus Rumah Makan Mie Ayam Bakso Solo) - Patrisia Moi; Kristianus Jago Tute; Benediktus Yoseph Bhae (Teknik Komputer Politeknik Negeri Sriwijaya, 2023)
Mie Ayam Bakso Solo Restaurant is a business engaged in the culinary business, namely the sale of food and beverages. However, at this time, information management is still using a manual system, namely data processing is still done by hand, so errors often occur in recording orders and payment transactions when payment transactions, the media used is a calculator so errors often occur, there are difficulties in making order reports. food, causing unclear details of income earned. The purpose of this information system is to process web-based food and beverage ordering data at the Mie Ayam Bakso Solo Restaurant to facilitate the work process, especially in the process of ordering food menus and transaction reports. The research method used to design a web-based food and beverage ordering information system is by conducting observations, interviews, and literature studies. The design method used in this research is the design method with the Unified Modeling Language (UML) model. While the system development method uses the Rapid Application Development (RAD) technique. The test method used is the Black-Box Testing method. The results achieved in this study are the formation of a web-based food and beverage ordering information system at the Mie Ayam Bakso Solo Restaurant which can facilitate the process of ordering food and drinks and transaction reports. Keywords: Information System, Ordering, UML, Web, RAD.